2020
DOI: 10.1002/ldr.3782
|View full text |Cite
|
Sign up to set email alerts
|

Soil phosphorus dynamics along a short‐term ecological restoration trajectory of a coastal sandplain forest in New Zealand

Abstract: We aim to understand the impact of ecological restoration on soil biogeochemistry, and the interrelationship between vegetation and soil phosphorus. In a study of two different‐aged soils in coastal New Zealand, soils are described along a transition from abandoned agricultural pasture, through 6‐year old restoration plots, towards forest fragments that have been largely undisturbed for 75 and 166 years. Soil biogeochemistry varied spatially along this restoration trajectory; there were profound changes in sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…The Sygera mountains distribute typical primordial dark coniferous forests growing at elevations ranging from 3700 to 4380 m above sea level in both sunny and shady slopes, making it an ideal area for comparing altitudinal patterns of soil stoichiometry at different slopes. Previous studies in Sygera mountains demonstrated that tree growth, plant communities, and soil bacterial communities change remarkably with the altitude [8][9][10][11]. However, current knowledge of the role of slope aspects on these changes as well as soil stoichiometry is limited.…”
Section: Introductionmentioning
confidence: 99%
“…The Sygera mountains distribute typical primordial dark coniferous forests growing at elevations ranging from 3700 to 4380 m above sea level in both sunny and shady slopes, making it an ideal area for comparing altitudinal patterns of soil stoichiometry at different slopes. Previous studies in Sygera mountains demonstrated that tree growth, plant communities, and soil bacterial communities change remarkably with the altitude [8][9][10][11]. However, current knowledge of the role of slope aspects on these changes as well as soil stoichiometry is limited.…”
Section: Introductionmentioning
confidence: 99%
“…This highlights the need for plant biomass as a coverage in reclaimed topsoils, aiming to protect it from erosion and facilitating nutrients recycling in the soil–plant system (Borges et al, 2019). Among these nutrients, phosphorus (P) stands out as a vital element for plant growth and development, despite its considerably low availability in tropical soils (Aleixo et al, 2020; Zhong et al, 2020). Several processes can cause this low availability, especially adsorption (Alovisi et al, 2020; Lu et al, 2017; Roy et al, 2017).…”
Section: Introductionmentioning
confidence: 99%